PERAN DIGITALISASI DALAM STRATEGI PEMULIHAN DAN KEBERLANJUTAN BISNIS UMKM TENUN SAMBAS PAUMIATI PASCA COVID-19 - Misbun Misbun (CV. Adiba Aisha Amira, 2025)
This study aims to examine the business dynamics of Sambas Paumiati Weaving MSMEs in Sambas Regency, West Kalimantan, which represents the economic resilience based on local culture in border areas. The main problem in this study is how traditional MSMEs can survive and thrive in the midst of modernization challenges and limited digital access. This study uses a qualitative approach with a case study method. Data was obtained through in-depth interviews with business actors, direct observation, and documentation of production and marketing activities. The results of the study show that the sustainability of this weaving business is supported by the strength of family social capital, cultural values, and the spirit of adaptation to change, although it still faces obstacles such as low digital literacy, limited market access, and suboptimal institutional support. These findings underscore the importance of a holistic and contextual empowerment approach, especially in strengthening the capacity of women MSME actors. This research also recommends the need for various parties in the mentoring and training process so that digital transformation can go hand in hand with the preservation of local culture. Thus, MSMEs such as Tenun Sambas Paumiati can become a model for developing a sustainable creative economy based on local wisdom